Evaluation of residual stresses in a pipe-to-plate welded joint by means of uncoupled thermal-structural simulation and experimental tests. (1st June 2021) - Chiocca, Andrea; Frendo, Francesco; Bertini, Leonardo
Highlights: A simplified thermal model has been introduced to simulate an arc-based welding process. The welding process of the pipe-to-plate joint was simulated by means of a an uncoupled thermal-structural simulation. Using the "element birth & death" technique, the correct solidification of the weld bead was simulated. Residual stresses were numerically evaluated over the entire volume of the component. Numerical results were validated by comparison of experimentally calculated relaxed strains. Graphical abstract: Abstract: A deep knowledge of the production process is needed, in order to achieve quality and safety requirements in a component. In this context, residual stresses play an important role, especially in welded structures. The present work deals with the assessment of residual stresses in a S355JR carbon steel pipe-to-plate welded joint. Both numerical simulations and experimental tests were employed in order to gain wide-ranging knowledge. Numerical simulations were performed with the software Ansys © through an uncoupled (one-way coupling) thermal-structural simulation in order to evaluate the stress, strain and temperature at each node of the finite element model for each phase of the simulation. Temperature-dependent elastic-plastic material properties were adopted in combination with the element birth & death method, necessary to simulate the welding process. Two numerical weld seam solidification methods were employed and discussed, in terms of expected results and simulation performances. The obtained numerical results were compared with experimental data of relaxed radial strains measured nearby the weld seam.